Comparison of lymphangiogenesis, lymphatic invasion, and axillary lymph node metastasis in breast carcinoma - Prerna Guleria; V Srinivas; D Basannar; Vibha Dutta (Wolters Kluwer Medknow Publications, 2018)
Context: Lymphangiogenesis correlates with poor prognosis in Invasive Ductal Carcinoma (IDC) breast. D2-40 antibody, a specific marker for lymphatic endothelium, differentiates lymphatic from vascular endothelium. Therefore, the aims of this study were to estimate lymphangiogenesis using D2-40 antibody and correlate with lymphatic invasion (LI) and axillary lymph node (LN) status and compare lymphatic mean vessel density (LMVD) with Tumor (T) and Node (N) stages and grade of tumor. Methods and Material: The study was conducted on fifty consecutive cases of IDC breast who underwent modified radical mastectomy (MRM) from Jan 2009 to March 2011. Hematoxylin-eosin sections and Immunohistochemistry (IHC) slides were studied along with their LN status. LMVD was counted after D2-40 immunostaining (100x magnification) in three hot spots in peritumoral areas and averaged. LI as opposed to vascular invasion (BVI), and LN status for all cases were assessed. Statistical Analysis: Statistical analysis was done using SPSS software (version 14.0 for Windows). Pearson's correlations, χ2 tests and Mann-Whitney U test were used. Results: Lymphangiogenesis varied from 0 to 58 with mean LMVD of 11. Of 50 cases, five showed no lymphatic vessels in peritumoral areas; of these five, three had positive LNs. 21/50 cases had LI. No statistical significant association was seen between lymphangiogenesis and LI. 34/50 cases had positive LNs. Mean LMVD was higher in patients with N2/N3 stage as compared to N0/N1 stage and was statistically significant (P = 0.013). Conclusions: D2-40 is specific marker for lymphatic endothelium. LI and lymphangiogenesis, as opposed to BVI, are better prognostic indicators in IDC breast.